Implementasi Aplikasi Harga Pokok Produksi pada UKM - Vini Mariani; Lianawati Christian; Henny Hendarti (Bina Nusantara University, 2015)
The accuracy of the production cost report is the basis of the control and decision making. Production cost affects the selling price of a product. The purpose of the study is to examine the procedures, forms, and reports relating to accounting information system production cost calculation in SMEs, analyze and design information systems that can support the planning and control of production information system ranging from production planning to report the cost of production by using The weighted average method. The methodologyused is the method of data collection, information and interviews. The method of designing the production cost is Object Oriented and Design. Program language used is Visual Basic. Implementation of the production cost applications in small and medium enterprises (SMEs) is to make application of MO estimation recording process and MO rate, cost card standard recording, WIP process recording, the quotation letter of raw materials, receipt of goods recording, the working hours card recording, cash expenditures recording, WIP transfer unit recording (work in process), the process of the final WIP units recording.